Antimicrobial Photodynamic Effectiveness of Light Emitting Diode (Led) For Inactivation on Staphylococcus aureus Bacteria and Wound Healing in Infectious Wound Mice. (March 2020) - Astuti, S D; Ardyana, Y; Arifianto, D; Winarno,; Puspita, P S; Yuwana, Y G Y; Pradhana, A A S
Abstract: This study aims to determine the effectiveness of the antimicrobial photodynamic therapy (aPDT) LEDs of 392 nm and 628 nm red LEDs for photoinactivation on Staphylococcus aureus in vitro and the photodynamic effectiveness of therapy for wound healing in mice in vivo. The sample used was Staphylococcus aureus bacterial isolate which was infected on mice incision wounds. The LED exposure was carried out at the energy density of 19.44 J/cm 2, respectively. In vitro test samples were divided into three groups, namely (P0): control group, (P1): LED treatment group 392 nm, (P2): LED treatment group 628 and (P3): LED combination treatment group 392 and 628 nm. In the in vivo test, the mice of infectious wound models were divided into 5 namely (M+): positive control group, (M-): negative control group, (M1): LED treatment group 392 nm, (M2): LED treatment group 628 and (M3): LED combination treatment group 392 and 628 nm. The results of in vitro studies showed an increase in the photoinactivation effect on LED exposure, with the effectiveness of inactivation on the LED 392 nm at 67.10%. The effect of photoinactivation of bacteria on wounds in vivo due to photodynamic therapy in the red LED exposure group was 88%, blue LED exposure group was 94%, exposure combination group of red and blue LEDs was 95%. So, the antimicrobial photodynamic therapy LEDs are effective for bacterial inactivation and accelerate wound healing in mice.